2015
DOI: 10.1080/10962247.2015.1040524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on removal of oxides of nitrogen by a photocatalytic coating

Abstract: Nitrogen oxides (NOx) emitted from combustion processes have elevated concentrations in large urban areas. They cause a range of adverse health effects, acid rain, and are precursors to formation of other atmospheric pollutants, such as ozone, peroxyacetyl nitrate, and inorganic aerosols. Photocatalytic materials containing a semi-conductor that can be activated by sunlight, such as titanium dioxide, have been studied for their ability to remove NOx. The study presented herein aims to elucidate the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, a study of photocatalytic stucco coatings found that the NOₓ removal rate decreased by increasing temperature from 30 °C to 40 °C when the relative humidity was low (20%), and remained constant for a higher relative humidity of 65%, suggesting that other factors-such as competition for surface sites with moisture and the nature of the substrate-may play a significant role [39]. A study of photocatalytic mortar also showed that increasing temperature from 20 °C to 30 °C led to a reduced removal rate for NO [8].…”
Section: Validation Using a Reference Photocatalytic Samplementioning
confidence: 99%
See 1 more Smart Citation
“…However, a study of photocatalytic stucco coatings found that the NOₓ removal rate decreased by increasing temperature from 30 °C to 40 °C when the relative humidity was low (20%), and remained constant for a higher relative humidity of 65%, suggesting that other factors-such as competition for surface sites with moisture and the nature of the substrate-may play a significant role [39]. A study of photocatalytic mortar also showed that increasing temperature from 20 °C to 30 °C led to a reduced removal rate for NO [8].…”
Section: Validation Using a Reference Photocatalytic Samplementioning
confidence: 99%
“…One study described faster NO oxidation as temperature rose from 5 to 60 °C [38]. Another study showed that the NOₓ removal rate decreased by increasing temperature from 30 °C to 40 °C at low relative humidity, but remained constant at a higher RH setting [39]. A third study observed a reduction in NO removal rates as temperature increased from 20 °C to 30 °C [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous work with pure TiO 2 nanoparticles reported, on average, higher NO and NO x abatements, but the experimental conditions are not comparable. In particular, the illumination in most of these works was strictly UV [68][69][70]. The current study also checked the photocatalytic effectiveness of the coatings once they were applied to the substrates.…”
Section: Characterization Of the Coatingsmentioning
confidence: 98%
“…Some previous work with pure TiO2 nanoparticles reported, on average, higher NO and NOx abatements, but the experimental conditions are not comparable. In particular, the illumination in most of these works was strictly UV [68][69][70].…”
Section: Characterization Of the Coatingsmentioning
confidence: 99%
“…26 Also on a photocatalytic cementitious coating the reaction of NO showed a negative temperature dependence from 30 1C to 40 1C at low humidity (20% RH). 27 Moreover, in an outdoor study decreasing NO x degradation on concrete was observed with increasing temperature. 8 A negative temperature dependence was also observed for the uptake of NO 2 on aluminum plates coated with a pure TiO 2 photocatalyst (P25) when the surface temperature was increased from 251 to 60 1C.…”
Section: Introductionmentioning
confidence: 95%